A Multilevel Analysis of Job Characteristics, Emotion Regulation, and Teacher Well-Being: A Job Demands-Resources Model - Yin, Hongbiao; Huang, Shenghua; Lv, Lijie (Frontiers in Psychology, 2018)
This study integrated personal factors into the job demands-resources model to examine school- and individual-level predictors of teacher well-being. Survey data were gathered from 1656 teachers from 54 schools. The results of hierarchical linear modeling indicated that the school-level emotional job demands of teaching and suppression at the individual level were positively related to teachers’ anxiety and depression whereas school-level trust in colleagues and individual-level reappraisal were positively associated with enthusiasm and contentment. Positive relationship between emotional job demands and suppression was also found. These findings support the claim that reappraisal should be considered a personal resource and suppression a personal demand.